The language of Saudi Arabia’s green economic transition: A discourse-historical analysis of metaphor, modality, and legitimation - Sa'di, Rami A; Koka, Nisar Ahmad (Research Journal in Advanced Humanities, 2026)
Saudi Arabia’s green economic transition is implemented through projects, finance, regulation, and institutional coordination, but it is also made publicly meaningful through language. This article examines how Arabic institutional discourse represents the transition, calibrates commitment, and justifies preferred actors and solutions. It applies a qualitative, corpus-assisted discourse-historical approach to 15 public Arabic source pages from the Saudi Green Initiatives, the Public Investment Fund, Saudi Aramco, and the Ministry of Energy. From those pages, 105 complete headlines, slogans, and policy clauses (804 Arabic tokens) were extracted as an analytical micro-corpus covering 2021–2025 and undated pages accessed in July 2026. Metaphor analysis identifies journey/transition as the largest family (46 units), followed by construction/materialization (24) and greening/growth/life (20). Modal choices combine obligation and formal commitment with future certainty, aspiration, and capacity, producing what the article calls managed certainty. Legitimation is led by rationalization (59 units), supported by moral evaluation, mythopoesis, and authorization. The discourse gives the transition a clear route, a capable institutional driver, measurable milestones, and a moral destination. It also humanizes policy through quality of life, future generations, jobs, and collective responsibility. Critically, however, citizens appear more often as beneficiaries or behavioural partners than as participants in deciding trade-offs. Labour adjustment, affordability, consumption, and distribution are less visible than technology, investment, supply, and national leadership. The article concludes that the discourse effectively joins climate action, energy security, and diversification, while a more inclusive next phase would make uncertainty, costs, accountability, and citizen agency more explicit.